Neglected yet pervasive: echinococcosis awareness and prevention capacity in Kyrgyzstan - Dmitry Vishniakov; Mairamkul Turdumambetova; Nazgul Matkerimova; Kenesh Dzhusupov; Zildiz Sultanbaeva; Eldar Rafibekov (Parasitology)
The study aimed to assess the heterogeneity in the distribution of disease awareness, attitudes, and practices related to cystic echinococcosis (CE) in different subgroups and inform health authorities regionally and globally for future evidence-based tailored prevention practices in the region. A cross-sectional study was conducted with 242 participants from Kyrgyz Republic (KR), Issyk-Kul oblast, and utilized survey data to analyse demographics, household information, echinococcosis-related practices, and knowledge. Participants in high-risk environments (HRE) and engaging in high-risk behaviours (HRB) linked to CE contracting were identified. Out of 242 participants, 39% lived in HRE, with 22% engaging in HRB of contracting CE. 13% lived in HRE and engaged in HRB. Only 6% followed all preventive measures, while 56% followed some. 97.5% of participants had heard about CE, but only 6% identified all transmission routes, and 63.4% were unaware of dog contact as a route. Education reduced the odds of being in the highest risk group (HRE&HRB) (OR 0.5, 95% CI 0.23–0.80). The study's findings are alarming, emphasizing factors contributing to regional endemicity. We anticipated a similar pattern in the neighbouring countries, given the shared nomadic customs and historical parallels. Examination of the heterogeneity of disease awareness and practices allows tailored prevention strategies. Urgent prevention programmes focusing on echinococcosis awareness in the KR are crucial to addressing challenges posed by nomadic habits.